Intellectual capital and the firm: evolution and research trends. Issue 4 (5th September 2019) - Martín-de Castro, Gregorio; Díez-Vial, Isabel; Delgado-Verde, Miriam
Abstract : Purpose: The phenomenon of intellectual capital in the firm has been deeply researched and immensely debated in the management literature in recent years. After three decades of evolution, it has become established as a mature field of research. At this point, a review of its theoretical foundations and current and future evolution provides us with the state of the art of intellectual capital in the firm. The purpose of this paper is to present a quantitative review of the existing literature on intellectual capital in the firm. Design/methodology/approach: In this paper, the authors present a quantitative review of the existing literature on intellectual capital in the firm. To do so, the authors searched the JCR-SSCI database from 1990 to 2016 and identified 553 citing documents; these were split into three main periods in order to identify the interactions and path dependencies existing between different foundations of research. In addition, areas of current and future research connected with the theoretical foundations were identified. For these purposes, the authors used both co-citation analyses as well as bibliographical coupling. Findings: In this paper, three main stages of IC evolution have been identified with the main topics and research frames, as well as their path dependencies. Additionally, four main areas of current and future development of IC have been identified: IC measurement, IC in new business models, IC disclosure, and its role in social capital and human resource practices. Research limitations/implications: The present bibliometric study is a quantitative review of papers published in the Web of Science database. Originality/value: By its dimensions ‒ broad academic disciplines and longitudinal character ‒ this bibliometric study constitutes a new quantitative review of the IC discipline, both drawing its intellectual evolution in the last decades, and showing current and future research trends in IC and the firm.